Evolution of digital activism on social media: opportunities and challenges - Castillo-Esparcia, Antonio; Caro-Castaño, Lucía; Almansa-Martínez, Ana María (Profesional de la Información, 2023)
The social media revolution has affected all areas, including activism. However, there is scepticism about its emancipatory capacity, and it is considered by some to be a distorted form of activism. This article presents a review of the existing literature on digital activism, starting with the concept itself, and examines its impact on the organisation of activists and citizen participation. Likewise, based on the platformisation of these spaces and the evolution of their affordances, we observe a growth in individual, strategic and low-commitment participation, the accentuation of the role of emotions in media that promote virality, and the assumption of playful forms of politainment by activists -especially on TikTok-. On the other hand, the strategies carried out by organisations to promote activism in relation to their causes are investigated, such as the generation of arguments provided by the interest group and the involvement in an action of dissemination, co-creation and replication of activists. Finally, the main challenges of digital activism are indicated: the growing inequality in terms of access to algorithmic visibility between activists and brands, influencers and interest groups; the desirability of complementing playful activism with work in alternative digital media that allows for more stable forms of collaboration; and the need to protect activists against the growth of hate speech on these platforms.
Evolución del activismo digital en los medios sociales: oportunidades y retos
Keywords: Redes sociales en Internet; Digital activism; Social networking sites; Social media; Affordances; Affective publics; Influencers; Virality; Datafication; Connective action; Data activism; Interest groups; Hacktivism; Clicktivism; Slacktivism